Angular‐Adaptive Reconfigurable Spin‐Locked Metasurface Retroreflector. Issue 21 (5th September 2021) - Yang, Weixu; Chen, Ke; Zheng, Yilin; Zhao, Wenbo; Hu, Qi; Qu, Kai; Jiang, Tian; Zhao, Junming; Feng, Yijun
Abstract: Metasurface retroreflectors, which scatter the incident electromagnetic wave back to incoming direction, have received significant attention due to their compelling advantages of low profile and light weight compared with conventional bulky retroreflection devices. However, the current metasurface retroreflectors still have limitations in wide‐angle and omnidirectional operations. This work proposes a high‐efficiency, wide‐angle, reconfigurable, and omnidirectional retroreflector composed of spin‐locked phase gradient metasurface with a thickness of only 5.2 mm or 0.07 operating wavelength. The reflection phase of constituent meta‐atoms can be controlled dynamically and continuously by altering their orientation states through individually addressing each mechanically rotational meta‐atom, whereas the reflection handedness is kept the same as incidence. Therefore, adaptive and arbitrary momentum can be imparted to the incident wave, providing high‐efficiency retroreflection over a wide continuous range from −47° to 47°. Moreover, such high‐performance retroreflection is extended to omnidirectional level, enabling great degrees of freedom that are unavailable by previous researches. As a proof of concept, a retroreflective metasurface is fabricated and experimentally demonstrated at microwave frequencies. The proposed thin thickness, high efficiency, and reconfigurable metasurface retroreflector can be extended to other frequencies that may offer an untapped platform toward reconfigurable spin‐based retroreflection devices for electromagnetic signal processing. Abstract : An angular‐adaptive spin‐locked retroreflector is realized using a reconfigurable metasurface composed of mechanically rotational meta‐atoms. The reflection phase of meta‐atoms can be controlled dynamically by altering the orientation states based on the Pancharatnam‐Berry phase. Therefore, adaptive and arbitrary momentum can be imparted to the incident wave, enabling high‐efficiency retroreflections over a large continuous range in an omnidirectional half‐space.